Calculation and determination of acquisition duty land and building rights - Putra, Adam Pramana; Darmawan, Arif; Suhartono, Slamet; Hufron, Hufron (Technium Social Sciences Journal, 2022)
The calculation and determination the land sales tax rate (BPHTB and PPH) for both seller and buyer is deemed unfair, because the calculation is based on market prices and not by sale value of tax objects. In addition, the calculation and determination of market prices doesn’t have a legal basis and unclear authority, and gives the impression of arbitrariness. Determination of market prices as basis for calculating BPHTB and PPh, only considers interests of increasing regional original income (PAD), without considering tax burden for sellers and buyers. Likewise, in determining NPOPTKP, it is felt to be unfair, because regardless with selling value, limit for NPOPTKP remains the same, even between regencies/cities the amount not much different.